Wildfire smoke triggers cirrus formation: Lidar observations over the Eastern Mediterranean (Cyprus) - Mamouri, Rodanthi-Elisavet; Ansmann, Albert; Ohneiser, Kevin; Knopf, Daniel A.; Nisantzi, Argyro; Buhl, Johannes; Engelmann, Ronny; Skupin, Annett; Seifert, Patric; Baars, Holger; Ene, Dragos; Wandinger, Ulla; et al. (My University, 2023)
The number of intense wildfires may increase in the upcoming years as a consequence of climate change. Changing aerosol conditions may lead to changes in regional and global cloud and precipitation pattern. One key aspect of research is presently whether or not wildfire smoke particles can initiate ice nucleation. We found strong evidence that aged smoke particles (dominated by organic aerosol particles) originating from wildfires in North America triggered significant ice nucleation at temperatures from−47 to −53°C and caused the formation of extended cirrus layers. Our study is based on lidar observations over Limassol, Cyprus, from 27 October to 3 November 2020 when extended wildfire smoke fields crossed the Mediterranean Basin from Portugal to Cyprus. The observations suggest that the ice crystals were nucleated just below the tropopause in the presence of smoke particles serving as ice-nucleating particles (INPs). The main part of the 2-3 km thick smoke layer was,however, in the lower stratosphere just above the tropopause. With actual radiosonde observations of temperature and relative humidity and lidar-derived smoke particle surface area concentrations as starting values, gravity wave simulations show that lofting by 90-180 m is sufficient to initiate significant ice nucleation on the smoke particles, expressed in ice crystal number concentrations of 1-100 L−1
Keywords: Wildfire; Smoke; Lidar; Cyprus; Atmospheric